Determination of stresses and forces arising during the technological process of stretching small-section pipes through a roller die using a mandrel tool - V. V. Timofeev; E. V. Patraev; I. V. Trifanov (Космические аппараты и технологии)
For the transmission of microwave energy and in various precision instruments, pipes with a small cross section are often used, which can be part of the waveguide paths of antenna-feeder devices of spacecraft. Drawing a tubular billet through a mandrel roller die is a reliable and technologically advanced method of manufacturing rectilinear sections of a waveguide path. The purpose of the study is to develop a methodology for calculating stresses in a tubular billet and drawing forces, taking into account friction and changes in the yield strength of materials. The study was conducted by mathematical modeling. The method of successive approximations was used for the calculation. An algorithm has been compiled and the basic formulas for determining the desired parameters are given. Calculations were carried out for pipes with a rectangular cross section of 3.6 x 1.8 mm made of M4 and L63 alloys, the forces arising during stretching in the mandrel, rolls and total stretching forces were determined. The patterns that arise during the technological process are identified and justified on the basis of calculations. The influence of the geometry and materials of the workpieces on the main technological parameters is definitely determined. The calculation model can be used to simulate the technological process in the manufacture of small-section pipes made of other metals, taking into account changes in their yield strength during deformation. The calculation method can be used to determine the rational modes of drawing pipes of small cross-section.